Effects of Concurrent Resistance and Aerobic Training on Body Composition, Muscular Strength and Maximum Oxygen Uptake in Men with Excess Weight - Namboonlue, Chaiyawat; Namboonlue, Sarocha; Sriwiset, Palakorn; Jaisuk, Jittima; Buttichak, Arunya; Muangritdech, Nattha; Saengjan, Wisutthida (Physical Education Theory and Methodology, 2023)
The study purpose was to compare the effects of concurrent resistance and aerobic training to resistance and/or aerobic training alone on body composition, muscular strength and maximum oxygen uptake in overweight and obese men. Materials and methods. Twenty-four overweight and obese (BMI = 23.0 – 29.9 kg/m2) volunteers who were male students from Ubon Ratchathani Rajabhat University, aged 19-22 years were assigned into 3 groups: 1) resistance training group (RT), 2) aerobic training group (AT) and 3) concurrent resistance and aerobic training group (RT+AT). The training was 45 minutes per session and 2 days per week. Body composition along with muscular strength (1-RM) and maximum oxygen uptake (VO2max) were measured before (2-3 days prior) and after (2-3 days post) a 5-week training period. Results. Waist circumference was significantly decreased in all three groups, but the RT+AT group also found improvement in percentages of fat-free mass (0.49 ± 0.49%, p = 0.021, mean ± SD) and skeletal muscle mass (1.01 ± 0.95%, p = 0.025) when compared to their baseline. Similarly, 1-RM in leg extension was significantly increased in all three groups, while the RT group (47.67 ± 14.85%, p = 0.01) and the RT+AT group (42.08 ± 21.70%, p = 0.039) showed a substantially larger improvement in the 1-RM in leg extension when compared to the AT group (20.37 ± 13.97%). Finally, VO2max was significantly increased in all three groups (baseline to post-intervention), though they were not significantly different between groups. Conclusions. Concurrent resistance and aerobic training can reduce waist circumference and increase fat-free mass, skeletal muscle mass, 1-RM and VO2max. Therefore, this training strategy may serve as a useful alternative way to improve overall physical fitness and health promotion in overweight to obese male population.